Ultrasound Improves Tissue Perfusion in Ischemic Tissue through a Nitric Oxide Dependent Mechanism - Suchkova, Valentina N.; Baggs, Raymond B.; Sahni, Sanjeev K.; Francis, Charles W. (Thrombosis and Haemostasis, 2002)
Ultrasound accelerates enzymatic fibrinolysis in vitro and in animal models and may be used as an adjunct to thrombolytic therapy. Ultrasound can also affect vascular tone directly, and we have now investigated the effect of ultrasound on tissue perfusion in a rabbit model of acute muscle ischemia to characterize the magnitude and temporal course of vasodilation and determine its mechanism. After ligation of the femoral artery of rabbits, tissue perfusion in the gracilis muscle as determined using a laser Doppler probe declined by 53% from 13.7 ± 0.3 U to 6.4 ± 0.2 U. The tissue became acidotic as pH declined from normal to 7.05 ± 0.2. Application of 40 kHz ultrasound at intensities from 0.25 to 0.75 W/cm2 progressively improved perfusion over 60 min and reversed acidosis, but these effects were both completely blocked by pre-treatment with the nitric oxide synthase inhibitor LNAME. Nitric oxide synthase activity in muscle was measured using an assay based on the conversion of radiolabeled L-arginine to L-citrulline and demonstrated an increase of 3.6-fold following ultrasound exposure. This effect was greatest at locations close to the transducer and declined progressively away from it. Histologic examination showed greater capillary circumference in ultrasound exposed muscle compared to unexposed tissue with no other histologic changes. We conclude that the application of 40 kHz at low intensity improves perfusion and reverses acidosis in acutely ischemic muscle through a nitric oxide dependent mechanism.
Keywords: Ultrasound; nitric oxide; nitric oxide synthase; ischemia